High anal swab viral load predisposes adverse clinical outcomes in severe COVID-19 patients. Issue 1 (1st January 2020) - Li, Haibo; Ren, Lili; Zhang, Lulu; Wang, Yeming; Guo, Li; Wang, Conghui; Xiao, Yan; Wang, Ying; Rao, Jian; Wang, Xinming; Liu, Ying; Huang, Chaolin; et al.
ABSTRACT: To identify the association between the kinetics of viral load and clinical outcome in severe coronavirus disease 2019 (COVID-19) patients, a retrospective study was performed by involved 188 hospitalized severe COVID-19 patients in the LOTUS China trial. Among the collected 578 paired throat swab (TS) and anal swab (AS) samples, viral RNA was detected in 193 (33.4%) TS and 121 (20.9%) AS. A higher viral RNA load was found in TS than that of AS, with means of 1.0 × 10 6 and 2.3 × 10 5 copies/ml, respectively. In non-survivors, the viral RNA in AS was detected earlier than that in survivors (median of 14 days vs 19 days, P = 0.007). The positivity and viral load in AS were higher in non-survivors than that of survivors at week 2 post symptom onset ( P = 0.006). A high initial viral load in AS was associated with death (OR 1.368, 95% CI 1.076–1.741, P = 0.011), admission to the intensive care unit (OR 1.237, 95% CI 1.001–1.528, P = 0.049) and need for invasive mechanical ventilation (OR 1.340, 95% CI 1.076–1.669, P = 0.009). Our findings indicated viral replication in extrapulmonary sites should be monitored intensively during antiviral therapy.